Sources of exposure identified through structured interviews of healthcare workers who test positive for severe acute respiratory coronavirus virus 2 (SARS-CoV-2): A prospective analysis at two teaching hospitals. Issue 1 (15th December 2021) - Rhee, Chanu; Baker, Meghan A.; Tucker, Robert; Griesbach, Diane; McDonald, Dinah; Williams, Sarah A.; Fiumara, Karen; Resnick, Andrew; Klompas, Michael
Abstract: We interviewed 1, 208 healthcare workers with positive SARS-CoV-2 tests between October 2020 and June 2021 to determine likely exposure sources. Overall, 689 (57.0%) had community exposures (479 from household members), 76 (6.3%) had hospital exposures (64 from other employees including 49 despite masking), 11 (0.9%) had community and hospital exposures, and 432 (35.8%) had no identifiable source of exposure.